Clarifying the atomic origin of electron killers in β-Ga2O3 from the first-principles study of electron capture rates. (1st November 2022) - Suo, Zhaojun; Wang, Linwang; Li, Shushen; Luo, Junwei
Abstract: The emerging wide bandgap semiconductor -Ga2 O3 has attracted great interest due to its promising applications for high-power electronic devices and solar-blind ultraviolet photodetectors. Deep-level defects in -Ga2 O3 have been intensively studied towards improving device performance. Deep-level signatures E 1, E 2, and E 3 with energy positions of 0.55–0.63, 0.74–0.81, and 1.01–1.10 eV below the conduction band minimum have frequently been observed and extensively investigated, but their atomic origins are still under debate. In this work, we attempt to clarify these deep-level signatures from the comparison of theoretically predicted electron capture cross-sections of suggested candidates, Ti and Fe substituting Ga on a tetrahedral site (TiGaI and FeGaI ) and an octahedral site (TiGaII and FeGaII ), to experimentally measured results. The first-principles approach predicted electron capture cross-sections of TiGaI and TiGaII defects are 8.56 × 10 –14 and 2.97 × 10 –13 cm 2, in good agreement with the experimental values of E 1 and E 3 centers, respectively. We, therefore, confirmed that E 1 and E 3 centers are indeed associated with TiGaI and TiGaII defects, respectively. Whereas the predicted electron capture cross-sections of FeGa defect are two orders of magnitude larger than the experimental value of the E 2, indicating E 2 may have other origins like CGa and Gai, rather than common believed FeGa .